2015
DOI: 10.3389/fphar.2015.00083
|View full text |Cite
|
Sign up to set email alerts
|

The depressor response to intracerebroventricular hypotonic saline is sensitive to TRPV4 antagonist RN1734

Abstract: Several reports have shown that the periventricular region of the brain, including the paraventricular nucleus (PVN), is critical to sensing and responding to changes in plasma osmolality. Further studies also implicate the transient receptor potential ion channel, type V4 (TRPV4) channel in this homeostatic behavior. In previous work we have shown that TRPV4 ion channels couple to calcium-activated potassium channels in the PVN to decrease action potential firing frequency in response to hypotonicity. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In a third study, Kinsman et al found no difference in water intake following hyperosmotic challenge between this latter model and controls. Besides these KO models, other studies linked TRPV4 to AVP secretion in SON [11], modulated thirst with a TRPV4 agonist [41], or showed its role in osmosensitivity of the PVN [13,14]. TRPV4 has also been described as a peripheral osmoreceptor in nerve endings surrounding hepatic blood vessels [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, Kinsman et al found no difference in water intake following hyperosmotic challenge between this latter model and controls. Besides these KO models, other studies linked TRPV4 to AVP secretion in SON [11], modulated thirst with a TRPV4 agonist [41], or showed its role in osmosensitivity of the PVN [13,14]. TRPV4 has also been described as a peripheral osmoreceptor in nerve endings surrounding hepatic blood vessels [19].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal TRPV4 channels may therefore be an important therapeutic target for cognitive, motor and ageing-related disorders. TRPV4 inhibitors have been described and were recently described as orally available compounds (Jia et al 2004;Krause et al 2005;Phan et al 2009;Vincent et al 2009;Morty & Kuebler, 2014;Feetham et al 2015;Qi et al 2015) and also as 'dual inhibitors' of TRPV4 and TRPA1 (Kanju et al 2016), which might be an attractive possibility given the postulated function of astrocytic TRPA1 (Lee et al 2012;Shigetomi et al 2012Shigetomi et al , 2013Wei et al 2016). Such inhibitors, if they are intended for oral use, will have to pass through the blood-brain barrier (although, for example, the blood-brain barrier is more penetrable in certain CNS disorders, such as multiple sclerosis).…”
Section: Role Of Trpv4 In Cns Neuronsmentioning
confidence: 99%
“…; Morty & Kuebler, ; Feetham et al . ; Qi et al . ) and also as ‘dual inhibitors’ of TRPV4 and TRPA1 (Kanju et al .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an in vivo study investigated whether hypotonic TRPV4 driven neuronal inhibition modulated cardiovascular parameters. In mice, intracerebroventricular administration of hypotonic solutions decreased mean blood pressure but not heart rate and inhibition of the TRPV4 channels abolished these effects (Feetham, Nunn & Barrett‐Jolley, ). These studies support a central TRPV4 channel as important for sensing osmolality and the authors proposed the effects of its activation to be mediated by the channel expressed on spinally projecting preautonomic neurons (Feetham, Nunn, Lewis, Dart, & Barrett‐Jolley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, TRPV4 and calcium activated potassium (K Ca ) ion channels have been shown to couple as osmosensors in the PVN in mouse brain slices and rat isolated PVN neurons (Feetham, Nunn, Lewis, Dart, & Barrett‐Jolley, ). Again in mice, intracerebroventricular administration of hypotonic artificial cerebrospinal fluid decreases blood pressure but not heart rate and inhibition of the TRPV4 ion channel attenuated this effect (Feetham, Nunn, & Barrett‐Jolley, ). While these studies demonstrate a functional role for TRPV4 in osmosensing within the PVN, they do not establish which neurons express the channel, leaving open the question of the neuronal mechanism underlying these observations.…”
Section: Introductionmentioning
confidence: 99%